Promoting quality of life through participation in Healthy Cities programme: sharing the experiences of Kuching city - Edris, Aishah (Universiti Putra Malaysia Press, 2003)
We live in an era where the issue of 'quality of life' is of prime concern with special reference to urban areas in the face of environmental and social deterioration, growing human insecurity and exposure to infectious and high risk diseases; not surprisingly, cities are blamed for the declining quality of life. The declining social and environmental conditions in urban areas warrant the need for swift solutions to be found and concrete measures/actions to be taken to arrest the further worsening of urban conditions. The Healthy Cities Movement was conceived as a result of the growing realization of the gravity of human-induced crisis that has besieged urban dwellers. It is in line with the spirit of Healthy Cities Movement that Kuching agreed to participate in the Healthy City Programme which began in 1995 and ended in 2000. The purpose to be served by this paper is to share the experiences of Kuching city in implementing the programme with a focus on how coordinated local action is achieved through multisectoral approach or 'smart partnership' which in turn engenders collaboration through community participation and inter-agency linkages. The information collated for the purpose of this paper is mostly derived from secondary sources.